CHALLENGE Concept: Verbal Presentation and Functioning in Fashion Discourse - K. A. Tkachenok (Научный диалог)
The means of verbalization of the concept of CHALLENGE and the functioning of its lexical representatives in the texts of glossy magazines are considered. The conceptual, axiological and figurative components of the concept are studied by the method of conceptual analysis. It is noted that the concept under study has a large number of verbal representatives, characterized by the originality of the semantic and structural peculiarities in texts about fashion. A comprehensive study of the concept of CHALLENGE is necessary in order to ensure the effectiveness of the impact on potential buyers - recipients of “fashionable” product. The analysis of lexical means and ways of presentation of this concept in the fashion discourse creates the basis to explore means of speech manipulation by the consciousness of the target audience to change and correct beliefs and attitudes of its representatives. Axiological component of the studied concept is commented. The author argues that the main structural elements of the conceptual component of the concept of CHALLENGE in texts of glossy magazines are “a challenge to the norms of behavior in society,” “challenge to the fashion,” “challenge to myself.” These data make a presentation about one of the most popular concepts prevalent in the minds of readers of glossy magazines.